Adverse effects of alternative therapy (minocycline, ofloxacin, and clofazimine) in multibacillary leprosy patients in a recognized health care unit in Manaus, Amazonas, Brazil Efeitos adversos das drogas (minociclina, ofloxacina e clofazimina) utilizadas no esquema alternativo para pacientes com hanseníase multibacilar, em unidade de referência, Manaus, Amazonas, Brasil - Marina Valente Maia; Maria da Graça Souza Cunha; Carolina Souza Cunha (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: After the introduction of the multidrug therapy, there was a decline in the coefficients of prevalence and detection of new cases of leprosy. However, the records of drug resistance and relapses are threatening factors in leprosy control. Hence, new alternative schemes and monitoring of adverse effects to avoid treatment abandonment are important considerations. OBJECTIVE: Describe the side effects of a multidrug regimen containing minocycline, ofloxacin, and clofazimine in multibacillary leprosy patients. METHODS: We conducted a prospective, descriptive, and observational study with multibacillary patients, including cases of intolerance to standard MDT and relapses. The study was carried out at Fundação Alfredo da Matta (Alfredo da Matta Foundation), in Manaus, Amazonas, from April 2010 to January 2012. The patients received alternative therapy, which consisted of daily self-administered doses of 100mg of minocycline, 400 mg of ofloxacin, and 50mg of clofazimine and a supervised monthly dose of 300mg of clofazimine for six months, followed by eighteen months of daily doses of ofloxacin 400mg, clofazimine 50mg, and a supervised monthly dose of clofazimine 300mg. Results: Twenty-one cases were included. Mild and transitory side effects occurred in 33.3% of patients. Of the total episodes, 45.9% were attributed to ofloxacin and they included abdominal pain, nausea, vomiting, headache, and insomnia; 21.6% were due to clofazimine, with 100% of patients presenting skin pigmentation. The mean time for the development of adverse effects after beginning the therapy was 15.2 days. CONCLUSION: All patients tolerated the drugs well, and compliance was satisfactory, with no serious events. Unlike other standard MDT studies had shown, no treatment was stopped due to side effects. Nevertheless, patient follow-up and studies with bigger samples are necessary to guarantee the efficacy and safety of the alternative regimen as a second-line scheme in multi-drug therapy. FUNDAMENTOS: Após introdução do esquema poliquimioterápico padrão, houve declínio nos coeficientes de prevalência e detecção de casos novos; entretanto, os registros de resistência medicamentosa e recidivas representam ameaça para o controle da hanseníase. Dessa forma, a proposição de novos esquemas alternativos e a necessidade de monitorar efeitos adversos são importantes para evitar o abandono do tratamento. OBJETIVO: Descrever efeitos adversos do esquema alternativo contendo clofazimina, ofloxacina e minociclina em pacientes com hanseníase multibacilar. MÉTODOS: Estudo prospectivo, descritivo e observacional de casos multibacilares, incluindo recidivas ou intolerância à poliquimioterapia padrão, realizado na Fundação Alfredo da Matta, Manaus, Amazonas, de abril de 2010 a janeiro de 2012. Os indivíduos receberam a terapia composta de doses diárias auto-administradas de 100mg de minociclina, 400mg de ofloxacina e 50mg de clofazimina e mensais supervisionadas de 300mg de clofazimina por seis meses, seguidas de 18 meses de doses diárias de ofloxacina 400mg, clofazimina 50 mg e supervisionadas mensais de clofazimina 300mg. Resultados: 21 pacientes foram incluídos. Efeitos adversos leves e transitórios foram observados em 33,3% dos pacientes; 45,9% foram atribuídos à ofloxacina, como dor abdominal, náuseas, vômitos, cefaléia e insônia; 21,6% foram associados à clofazimina, com relatos e observação em 100% dos pacientes de hiperpigmentação cutânea. O tempo médio de desenvolvimento das reações adversas a partir do início do esquema foi de 15,2 dias. CONCLUSÃO: A adesão e regularidade ao esquema foram satisfatórias, com boa tolerabilidade, sem casos de interrupção ao tratamento. Todavia, há necessidade de acompanhamento dos indivíduos e aumento do número amostral para garantir a eficácia e segurança em longo prazo.